Photoredox One-Pot Synthesis of 3,4-Dihydroquinolin-2(1H)-ones - He, Jing-Yao; Bai, Qi-Fan; Li, Xuewen; Shou, Jianxin; Feng, Gaofeng (Synlett, 2022)
A photoredox one-pot strategy for efficient accessing 3,4-dihydroquinolin-2(1H)-ones from anilines, oxalyl chloride, and electron-deficient alkenes is disclosed. The new approach features excellent synthetic efficiency, readily available starting materials, and simple operations. It is compatible with a variety of anilines and electron-deficient alkenes. A broad array of 3,4-dihydroquinolin-2(1H)-ones were prepared.
Keywords: 3,4-dihydroquinolin-2(1H)-one; photoredox catalysis; one-pot synthesis; efficient synthesis; oxalyl chloride